Targeting ocular malignancies using a novel light-activated virus-like drug conjugate - Sen Ma; Ruben V. Huis In't Veld; Elisabet de los Pinos; Ferry A. Ossendorp; Martine J. Jager (Advances in Ophthalmology Practice and Research)
Background: Targeted therapy is a promising approach to improve the treatment of tumors, including ocular malignancies. Current therapies, such as radiotherapy and surgery, often lead to serious damage to vision or to loss of the eye. New approaches have examined nanoparticles for use as targeted delivery vehicles for drugs. A newly-developed virus-like drug conjugate is a promising nanoparticle with a defined target: the novel virus-like particle-photosensitizer conjugate Belzupacap sarotalocan (Bel-sar, previous name AU-011). Main text: In this review, we summarize the application of this novel light-activated virus-like particle conjugate in pre-clinical and clinical studies and discuss its potential to treat ocular malignancies, such as uveal melanoma and conjunctival melanoma. We furthermore discuss the combination with immunotherapy and its application on pigmented and non-pigmented tumors as well as its effect on macrophage polarization, which is important to achieve effective results in immunotherapy. Conclusions: Belzupacap sarotalocan (Bel-sar) is a promising targeted drug carrier that enhances tumor-specific delivery and minimizes off-target effects. Its photodynamic therapy effectively treats pigmented and non-pigmented tumors while inducing immunogenic cell death through DAMP exposure, triggering local and systemic immune responses. Combining Bel-sar PDT with immunotherapy improves efficacy in preclinical models, warranting further clinical investigation.